2021
DOI: 10.3390/healthcare9081007
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Digitalisation and the Changing Nature of Work and Society

Abstract: Digital technologies have profound effects on all areas of modern life, including the workplace. Certain forms of digitalisation entail simply exchanging digital files for paper, while more complex instances involve machines performing a wide variety of tasks on behalf of humans. While some are wary of the displacement of humans that occurs when, for example, robots perform tasks previously performed by humans, others argue that robots only perform the tasks that robots should have carried out in the very firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 53 publications
1
23
0
3
Order By: Relevance
“…This should help to alleviate geographic inequities in healthcare access; however, the opposite effect, due to lack of digital literacy or affordability of the devices, is a risk. It has been reported that AI will also benefit from the digitalization of healthcare and allow for automated decision support for healthcare professionals in patient diagnosis, counsel and treatment ( 51 ). Finally, medicines regulators may be able to use real-world date to monitor medicines effectiveness in the real-world ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…This should help to alleviate geographic inequities in healthcare access; however, the opposite effect, due to lack of digital literacy or affordability of the devices, is a risk. It has been reported that AI will also benefit from the digitalization of healthcare and allow for automated decision support for healthcare professionals in patient diagnosis, counsel and treatment ( 51 ). Finally, medicines regulators may be able to use real-world date to monitor medicines effectiveness in the real-world ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, a considerable number of the managing directors apprehended obstacles, such as the lack of investment budgets and the lack of infrastructure for continuous information processing, as restraining factors. Sætra and Fosch-Villaronga [ 47 ] critically discussed the changing nature of digitalization in healthcare. They introduced a three-level framework in which it is stated that skills and jobs are transforming, but the quality and quantity of care are on different levels.…”
Section: Discussionmentioning
confidence: 99%
“…Just as the robot rights movement is often perceived as a form of unwarranted and misdirected activism (Birhane and Van Dijk, 2020a;Birhane and Van Dijk, 2020b), the same often goes for environmental ethicists, at times labeled "treehuggers," antihumanists or misanthropes who fight for the rights of animals and the natural world at the expense of human beings (Drengson, 1995;Kopnina et al, 2018;Rottman et al, 2021). Such a denouncement is, however, based on the erroneous notion that there is a "hierarchy of ethics" and that all research should be directed to whichever problems the critics consider to be more important than considering robot-or environmental-rights (Saetra and Fosch-Villaronga, 2021).…”
Section: Anthropocentrism and The Othersmentioning
confidence: 99%